3D heterogeneous integrated systems: Liquid cooling, power delivery, and implementation - Bakir, M.S.; King, C.; Sekar, D.; Thacker, H.; Bing Dang; Gang Huang; Naeemi, A.; Meindl, J.D. (2008 IEEE Custom Integrated Circuits Conference, 2008)
This paper describes a novel 3D integration technology that enables the integration of electrical, optical, and microfluidic interconnects in a 3D die stack. The electrical interconnects are used to provide power delivery and signaling, the optical interconnects are used to enable optical signal routing to all levels of the 3D stack, and the microfluidic interconnects are used to cool each level in the 3D stack and thus enable stacking of high-performance (high-power) dice. These interconnects are integrated in a 3D stack both as through-silicon vias (TSVs) and as input/output (I/O) interconnects. Design trade-offs (TSV density, power supply noise, thermal resistance, and pump size), fabrication, and assembly are reported.